Emerging Trends in Engineering Intelligent Systems for Sustainable Development - P. V. Narendra Kumar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The increasing demand for sustainable development has catapulted the development of intelligent systems, which are set to play a crucial role in various issues affecting the entire world including effects of climate change, explosive depletion of resources and urbanization. This paper discusses the emerging trends in the engineering, which is oriented towards using the intelligent systems to bring sustainability to different areas. It goes into integration of artificial intelligence (AI), machine learning (ML), and the Internet of Things (IoT) to provide solutions in energy efficiency, waste management, smart cities, and green technologies. The research explores the developments that are underway in these fields, presenting case studies, methodologies, and results that reflect the influence of intelligent systems on the sustainable practices. The paper ends with identification of the future directions and barriers of intelligent systems use for long-term sustainability.